Medical tourism research: A conceptual framework of emerging business strategies in healthcare industry - Krishnan, Thilagavathi; Chelliah, Shankar (2013)
Malaysia is in the progress of diversifying its economic activities towards a service-based economy to create highly payable jobs and to achieve a developed nation status by 2020. At the same time, the world had recognized healthcare sector as a highly potential global industry Therefore, based on the available resources in the country and the changing trend of the world economy, Malaysia noticeably recognizing healthcare travel as one of the new source of sustainable economic activity. Malaysia’s effort in promoting medical tourism industry is being materialized through the strategies adopted by the healthcare centers in the country. Looking into this opportunity, academic research is needed to device strategies to gain competitive advantage in medical tourism industry in the region. Therefore, the purpose of the study is to examine the factors that contribute to the growth of the medical tourism industry in Malaysia by studying the medical tourists’ satisfaction from the aspects of medical cost, quality healthcare services, specialist medical services, government regulations and contribution of medical tourism agents. Medical cost, quality healthcare services and specialist medical services are identified as internal factors within the control of the healthcare centers. Government regulations and contribution of medical tourism agents are defined as the external factors that are not regulated by the healthcare providers. This study is designed to see the relationship between internal factors and external factors on medical tourists’ satisfaction using resource based view (RBV) theory and adopting Porter’s Competitive Advantage Model. The practical implication of the study is focused to the management of the international healthcare providers in adopting strategies in achieving greater medical tourists’ satisfaction.